(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The purpose of this research is to determine the approach in and extend to which consumers’ environmental attitudes affect their purchasing behavior. In this competitive edge companies are persistently trying to discover the best ways to get the attention of customers and reach them for increasing growth of business. Thus, they are becoming Environment friendly by implementing the concept of green marketing. Today’s Customers are becoming more aware and demanding so that they have started to pay more attention to the environment also. The main objective of this paper is to find out how consumer (buying) behaviour is influenced by Green Marketing through Companies. Green marketing is a tool of protecting the environment for the future creation. It has a positive impact on environmental safety, because of the growing concern of environmental protection. Green marketing is a materialization of a new market. The customers are becoming more eco-responsible and customers are concerned about environmental issues in new market. For companies to survive in this new competitive market, they must find an opportunity to enhance product's performance and strengthen customer's loyalty to command a higher price. As such, green marketing is not just an environmental protection tool but also, a marketing strategy.